Abnormal conduction and morphology in the atrioventricular node of mice with atrioventricular canal targeted deletion of Alk3/Bmpr1a receptor. - Stroud,DM; Gaussin,V; Burch,JBE; Yu,C; Mishina,Y; Schneider,MD; Fishman,GI; Morley,GE (Circulation, 2007)
BACKGROUND: The atrioventricular (AV) node is essential for the sequential excitation and optimized contraction of the adult multichambered heart; however, relatively little is known about its formation from the embryonic AV canal. A recent study demonstrated that signaling by Alk3, the type 1a receptor for bone morphogenetic proteins, in the myocardium of the AV canal was required for the development of both the AV valves and annulus fibrosus. To test the hypothesis that bone morphogenetic protein signaling also plays a role in AV node formation, we investigated conduction system function and AV node morphology in adult mice with conditional deletion of Alk3 in the AV canal. METHODS AND RESULTS: High-resolution optical mapping with correlative histological analysis of 28 mutant hearts revealed 4 basic phenotypic classes based on electrical activation patterns and volume-conducted ECGs. The frequency of AV node conduction and morphological abnormalities increased from no detectable anomalies (class I) to severe defects (class IV), which included the presence of bypass tracts, abnormal ventricular activation patterns, fibrosis of the AV node, and twin AV nodes. CONCLUSIONS: The present findings demonstrate that bone morphogenetic protein signaling is required in the myocardium of the AV canal for proper AV junction development, including the AV node.